Study of a Novel Ceramic Tool Performance in the Machining of Ti-6Al-7Nb Alloys. (2019) - del Risco-Alfonso, Ricardo; Siller, Hector R.; Pérez-Rodríguez, Roberto; Molina, Arturo
ABSTRACT: Considering their distinctive properties, titanium alloys are used in foremost industries, including the aeronautic, automotive and biomedical industries. The reduced machinability of titanium alloys is due to their low thermal conductivity and high plasticity behavior. In the biomedical sector, one of the most studied alloys is Ti-6Al-4V. In the case of the Ti-6Al-7Nb alloy, scarce investigations are identified, related to machinability studies. The machining of Ti-6Al-7Nb alloy requires the development of new tools with higher properties, which provide better performance. The objective of this study is to present the experimental results related to a novel ceramic cutting tool, in terms of cutting tool life and productivity, in the machining of Ti-6Al-7Nb alloy. A turning operation of a 25 mm diameter bar was performed; the cutting speed was varied in three levels. The results showed the high performance of this type of tools, from the point of view of machinability. The values of the obtained cutting forces are found in the ranges reported by the consulted literature using ceramic tools. The surface roughness values were considered appropriate, taking into account that the tool is recommended for roughing and semi-finishing operations. The most relevant results were obtained in terms of productivity, considering that the performance is 2.53 times higher than the presented in similar works.